Geography And Social Movement : Comparing Antinuclear Activism in the Boston Area - Miller, Byron A., 1957- (Book collections on Project MUSE., 2000)
Byron A. Miller directly addresses the implications of space, place, and scale in social movement mobilization, and then demonstrates their significance in a detailed comparative analysis of peace movements in three municipalities around Boston.